Activating Unconstitutional Norms in Law: An Analysis of the Principle of Checks and Balances: Menghidupkan Norma Inkonstitusional dalam Undang-Undang: Suatu Analisis Prinsip Checks and Balances - Costantinus Fatlolon (Jurnal Konstitusi, 2023)
The existence of norms in the law that have been declared unconstitutional by the Constitutional Court, but re-included in the process of forming laws, can cause harm to the rights of citizens that have been guaranteed by the 1945 Constitution, especially if they are placed in the concept of checks and balances. This study has two objectives, namely, first, to analyze the concept of checks and balances and examples of norms that were canceled by the Constitutional Court but revived. Second, the implications of bringing unconstitutional norms to life. This research was conducted using normative juridical research. The results showed that the principle of checks and balances requires that legislative, executive, and judicial powers control each other. Some unconstitutional norms, but re-enacted, are spread through some statutes. The consequences if an unconstitutional article is reinserted into the law, it will threaten the system of checks and balances that have been agreed upon and affirmed in the 1945 NRI Constitution. In order to apply the principle of checks and balances, reviving an unconstitutional clause that has been overturned by the Constitutional Court must be rejected.